International Journal of Colorectal Disease c - Pellino, Gianluca; Germer, Christoph-Thomas.; SpringerLink (Online service) (Berlin/Heidelberg : Springer Berlin Heidelberg : Imprint: Springer.)
The International Journal of Colorectal Disease aims to publish novel and state-of-the-art papers which deal with the physiology and pathophysiology of diseases involving the entire gastrointestinal tract. In addition to original research articles, the following categories will be included: reviews (usually commissioned but may also be submitted), case reports, letters to the editor, and protocols on clinical studies. The journal offers its readers an interdisciplinary forum for clinical science and molecular research related to gastrointestinal disease. .
Keywords: Surgery; Internal medicine; Gastroenterology; Colon (Anatomy)$1 (BSurgery.s; Proctology; Surgery; Internal Medicine; Gastroenterology; Colorectal Surgery; Proctology